Remote monitoring system for livestock environmental information based on LoRa wireless ad hoc network technology - Fu, Xiao; Shen, Weizheng; Yin, Yanling; Zhang, Yu; Yan, Shichao; Kou, Shengli; Qu, Tengyu; Jacqueline, Musabimana (International Journal of Agricultural and Biological Engineering, 2022)
The environmental quality of livestock houses is key to livestock breeding and directly affects the growth and health of animals. To target the characteristics of long application cycles and large coverage areas for environmental monitoring in large-scale livestock breeding, the current study designed a remote monitoring system to provide livestock environmental information based on LoRa wireless ad hoc network technology. The system consisted of collection terminals, control terminals, LoRa gateways, and Alibaba Elastic Compute Service. It realized real-time collection, wireless transmission, storage of multi-sensor node data, and remote control. The system was not limited by the selected time or region, because data interaction was achieved by accessing cloud servers using GPRS technology. Users could browse and obtain data from computers and a WeChat mini program from any location with network coverage. Additionally, the system used the improved receiver-based auto rate (RBAR) rate-adaptive algorithm in the LoRa wireless communication component. After application on a dairy farm, the results showed that the whole system collected 6140 sets of environmental data from four dairy houses. The packet loss rate was less than 1% within a communication distance of 604 m, and the communication success rate was greater than 99%. The control instructions were real-time and accurate, and the response time was less than 10 s, which met the remote control needs of large farms. The system provided powerful data and technical support for precision animal production. Keywords: remote monitoring, LoRa wireless ad hoc network, livestock environment, environment information, system DOI: 10.25165/j.ijabe.20221504.6708 Citation: Fu X, Shen W Z, Yin Y L, Zhang Y, Yan S C, Kou S L, et al. Remote monitoring system for livestock environmental information based on LoRa wireless ad hoc network technology. Int J Agric & Biol Eng, 2022; 15(4): 79–89.